2001
DOI: 10.1038/sj.cdd.4400851
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the necrotic cleavage of poly(ADP-ribose) polymerase (PARP-1): implication of lysosomal proteases

Abstract: The poly(ADP-ribose) polymerase (PARP-1), a 113 kDa nuclear enzyme, is cleaved in fragments of 89 and 24 kDa during apoptosis. This cleavage has become a useful hallmark of apoptosis and has been shown to be done by DEVD-ase caspases, a family of proteases activated during apoptosis. Interestingly, PARP-1 is also processed during necrosis but a major fragment of 50 kDa is observed. This event is not inhibited by zVAD-fmk, a broad spectrum caspase inhibitor, suggesting that these proteases are not implicated in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
222
1
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 295 publications
(246 citation statements)
references
References 21 publications
14
222
1
1
Order By: Relevance
“…The specific cathepsin L inhibitor Z-FY-CHO inhibited cathepsin L-mediated cleavage of purified and nuclear topo I (Figures 3C and D). The concentration ranges of cathepsins and the incubation conditions used in these experiments were based on reported studies (26,27). It should be noted that untreated topo I, either in purified form or in the isolated nuclei, underwent limited degradation into a 70-kd product during protein or nuclear preparation (Figure 3), consistent with previous reports (3)(4)(5).…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…The specific cathepsin L inhibitor Z-FY-CHO inhibited cathepsin L-mediated cleavage of purified and nuclear topo I (Figures 3C and D). The concentration ranges of cathepsins and the incubation conditions used in these experiments were based on reported studies (26,27). It should be noted that untreated topo I, either in purified form or in the isolated nuclei, underwent limited degradation into a 70-kd product during protein or nuclear preparation (Figure 3), consistent with previous reports (3)(4)(5).…”
Section: Resultssupporting
confidence: 86%
“…A previous report implicated cathepsins B and G in the necrotic cleavage of PARP, a lupus-associated autoantigen (26). Our results indicated that cathepsins B, G, H, and L can induce topo I fragmentation in vitro.…”
Section: Discussionsupporting
confidence: 72%
“…The 50 kDa fragment was designated as a major necrotic fragment. [38][39][40] From these results, we confirmed that the death of HepG2 cells induced by CCl 4 is predominantly due to necrosis.…”
Section: Necrosis In Hepg2 Induced By CCLmentioning
confidence: 53%
“…Detection of a 50 kDa fragment derived from PARP-1 in CCl 4 -treated cells is strong evidence for necrosis, because the apoptotic PARP-1 fragment of 85 kDa induced with TNFa/CHX is distinct from the 50 kDa fragment 38,39 (Figure 1d). These results clearly indicated that a majority of HepG2 cells exposed to CCl 4 died in a necrotic manner, with a good agreement with previous results.…”
Section: Discussionmentioning
confidence: 99%
“…23 One possibility is that cathepsins could nonspecifically degrade important cellular proteins, thereby causing the cell to initiate apoptosis. 24 Alternatively, cathepsins could cleave and activate caspases or their downstream death effector substrates, 25 thereby causing apoptosis. In support of the former mechanism, it has been shown that cathepsin B can activate the inflammatory caspases 1 and 11, 17,26 and that cathepsin L may activate caspase-3.…”
Section: Introductionmentioning
confidence: 99%